A Sytematic Literature Riview (SLR) : Family Hope Program (PKH) in Indonesia - Elvany, Ghea amelia; Akbar, Gugun Geusan; Karmila, Mila (ann4publisher@gmail.com, 2024)
A systematic Literature Review is important for making decisions on social science. An analysis of 20 articles published between 2010 and 2023 shows an increase in publications on the Family Hope Program, with the number of articles published peaking in 20 at five articles. This increase indicates a growth in research interest in the topic. In the search for research methods used in 20 articles related to the Family Hope Program, most research adopts a quantitative approach, while the qualitative approach tends to be rarely applied. Of the 20 articles analyzed, 9 obtained a significant number of citations compared to others, indicating that the topic of the Family Hope Program is still not widely used as a reference by other researchers. The analysis also reveals that universities publish the majority of the articles related to this topic. However, this also presents an opportunity for other institutions, such as innovation agencies and research agencies, to contribute more to the research and discussion on the Family Hope Program. This underscores the potential for broader involvement in future research and discussion on the Family Hope Program.